Contaminación del agua por plaguicidas en un área de Antioquia (2010)
ABSTRACT: Determining the frequency of pesticide use in agricultural, pig and poultry production to understand its influence on water resources in the village of Monterredondo in the municipality of San Pedro de Los Milagros (Antioquia) and diagnosing its quality Methods 100 % of the households in the village were surveyed regarding chemical use. Physicochemical and microbiological analysis of three water samples was carried out in the Universidad de Antioquia's Environmental Engineering laboratory using standardised methods. Results The Hato stream was contaminated by 1,600x103 NMP/100ml coliforms and 220x10 NMP/100ml E. coli. The Fray Juana stream had 1,600x103 NMP/100ml coliform contamination. Water sources were also contaminated by the use of pesticides such as Lorsban (chlorpyriphs), Burst (chlorpyriphs), Whip (chlorpyriphs), Neguvon (metriphonate) and Furadan (carbophuran) and insecticides like Ganabaño (cypermethryn) and disinfectants and Limpido (6 % sodium hypochlorite). Conclusion Agricultural, pig and poultry production in the village has been producing a negative impact on water resources due to its reduced availability and pollution. The water from the samples analysed here was not suitable for human consumption.